Avaliação do escurecimento do tegumento de genótipos de feijão carioca durante o armazenamento - Ariati, Ana Claudia (2018)
The Common bean (Phaseolus vulgaris L.) is a species of great nutritional and economic importance. The genotypes of the carioca group vary in relation to integument darkening speed, which is a determinant factor in their acceptability by the consumer market. The objective of this work was to characterize carioca-bean genotypes during q 120 day storage period under accelerated aging conditions. The experiment was conducted in the experimental area of UTFPR - Pato Branco, in a randomized block design, with four replicates and ten genotypes: IPR Curió, BRS Estilo, IAC Emperor, BRSMG Madrepérola, IAC Milênio, BRS Requinte, ANFc 9, TAA Dama, Pearl and IPR Tangará. After physiological maturity the plots were plucked, trodden, dried and cleaned, then stored under accelerated aging conditions, at a temperature of 40ºC ± 3 and a relative humidity of 75% ± 3. Soon after the harvest and at 15, 30, 60, 90 and 120 days of storage, grain integument color was evaluated using the CIELab system, while the values for luminosity L *, chromaticity a * and b *, total color difference (ΔE *) and darkening index (IE), water absorption capacity during twelve hours of imbibition, mass of a thousand grains (MMG) and the total soluble proteins present in the integument of the grains were also evaluated. Additionally, a protein prediction model of carioca bean integument was constructed, using two different granulometries: bran and flour, using NIRS (Near Infrared Spectroscopy). The preparation of the samples for NIRS consisted of the crushing of the whole grain in flour and bran. For the samples, two methods of prediction, Cross Validation and Test Set, were used to compare the two models and to evaluate the best prediction of protein contents. All evaluated genotypes were susceptible to integument darkening, but to different intensities. The values of luminosity presented decreases during storage, whereas the chromaticity a * and darkening index increased and the chromaticity b * decreased for the genotypes with lower luminosity values. The percentage of water uptake by the grains during the storage presented decreases for most of the evaluated genotypes. The chromaticity a * and b *, and water absorption capacity were the main contributors to the divergence between genotypes after storage. However, the genotypes with the highest darkening intensity were not always the ones with the lowest water absorption capacity. After 120 days of storage, BRSMG Madrepérola had the lowest ABS content, a lower chromaticity a * value and higher chromaticity b * value, while TAA Dama presented high values of b * chromaticity. BRS Estilo and IAC Milênio had a higher ABS content. For the construction of the prediction model, the granulometry denominated as flour was more efficient for the construction of the prediction algorithms, by generating more homogeneous spectra, and the prediction model that presented the best indexes was the Test Set.